How I Reached the Age of 65 with a Congenital Heart Disease and Atherosclerosis - Gabaev, Delik D (International Journal of Innovative Research in Medical Science, 2016)
At me congenital disease of heart and the got atherosclerosis. In this publication I describe what mode of a life and what diet have helped me without medical assistance and medicines to live till 65 years and not to go on the old-age pension.